Genetic Variability, Correlation and Path Analysis of Different Hill-Rice (Oryza Sativa) Genotypes (Global Journal of Science Frontier Research, 2019)
Rice (Oryza sativa), a staple food crop is central to the lives of people around the world. Present production of rice will not suffice rapidly increasing population as the area for production is decreasing. This necessitate to increase the productivity of rice through crop improvement. In order to identify suitable traits that contribute for crop improvement through the estimation of genetic variability, correlation and path coefficient analysis an experiment on eleven rice genotypes was conducted in randomized complete block design (RCBD) with three replications under irrigated condition at Institute of Agriculture and Animal science, Lamjung. Analysis of Variance revealed that genotypes under study differed significantly for all the traits under study which implies that genotypes constitute a pool of germplasm with adequate variability. The phenotypic coefficient of variation (PCV) values were higher than genotypic coefficient of variation (GCV), revealing lower influence of environment in character expression. High heritability coupled with high genetic advance and moderate GCV were observed for leaf area, number of effective tillers per m 2 and days to 50% flowering.
Keywords: correlation; GCV; genetic advance; heritability; path analysis